Физико-механические характаристики аморфных углеродных пленок, полученных из паров бензола - Грицкевич, Р.Н.; Куцай, А.М.; Дуб, С.Н.; Шпак, Е.П.; Гонтарь, А.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The structural and physical properties analysis of amorphous carbon film produce in focus on the diamond-like type by the low temperature chemical vapour deposition from benzol have been presented. The diamond-like amorphous carbon films proposed as protective, wear-resistive and chemical inert coatings for the application in machine-building.